Improving Voice Outcomes After Thyroid Surgery – Review of Safety Parameters for Using Energy-Based Devices Near the Recurrent Laryngeal Nerve - Wang, Jia Joanna; Huang, Tzu-Yen; Wu, Che-Wei; Lin, Yi-Chu; Tseng, Hsin-Yi; Liu, Cheng-Hsin; Lu, I-Cheng; Chang, Pi-Ying; Chen, Hui-Chun; Chen, Hsiu-Ya; Dionigi, Gianlorenzo; Chiang, Feng-Yu; et al. (Frontiers in Endocrinology, 2021)
Technological advances in thyroid surgery have rapidly increased in recent decades. Specifically, recently developed energy-based devices (EBDs) now enable simultaneous dissection and hemostasis. Observed advantages of EBDs in thyroid surgery include their considerable reduction of operative time, incision length, blood loss, and post-operative pain; their most important advantage is their significantly lower rate of postoperative neck hematoma and postoperative hypocalcemia. However, the rate of recurrent laryngeal nerve (RLN) injury during EBD use has shown statistically inconsistent. Specifically, lateral thermal spread of residual heat generated at the high temperatures required for EBD use can cause iatrogenic thermal injury to the RLN. This article reviews relevant medical literature published on two safety parameters for EBD use in thyroid surgery: safe distance and cooling time. To improve voice outcomes in the quality-of-life era, surgeons should observe safety parameters and follow the standard procedures when using EBDs near the RLN in thyroid surgery